2006
DOI: 10.1007/s00125-006-0290-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of diabetes prevention studies: questionnaire survey of professionals in diabetes care

Abstract: Aims/hypothesis: Diabetes prevention studies have reported reductions of diabetes risk by up to 60%. Since the underlying metabolic changes are small, the clinical significance of this effect may be overestimated. The present survey explores the extent to which different formats of presenting study results may influence diabetes healthcare professionals' perceptions of the importance of intervention effects on diabetes risk. Subjects, materials and methods: Participants of three European diabetes conferences (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 21 publications
1
31
0
5
Order By: Relevance
“…The consequences of this negligence are reflected in several studies that found many doctors of different specialties suffer from statistical illiteracy (e.g. [30][31][32][33][34]), which in turn makes them unlikely to provide transparent numerical risk information to their patients. From our own experience in teaching doctors, we know that it takes little time and expense to teach them the difference between absolute and relative risk, and to make them aware of the phenomenon of mismatched framing.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…The consequences of this negligence are reflected in several studies that found many doctors of different specialties suffer from statistical illiteracy (e.g. [30][31][32][33][34]), which in turn makes them unlikely to provide transparent numerical risk information to their patients. From our own experience in teaching doctors, we know that it takes little time and expense to teach them the difference between absolute and relative risk, and to make them aware of the phenomenon of mismatched framing.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…Since then, a reduction of diabetes risk by more than 50% has been publicly claimed and large-scale population intervention is being promoted [3]. A Canadian study about the attitudes of pharmacists toward diabetes and its management concluded that pharmacists agree that they should be part of the health-care team for managing diabetes and should be required to have specialized training to provide primary diabetes care [4].…”
Section: Diabetes Mellitus Affects Approximately 1 Inmentioning
confidence: 99%
“…These concerns appear to reflect a rather paternalistic attitude, as medical and other healthcare professionals cannot be assumed to possess critical health literacy skills and therefore might 'hinder' an evidencebased process to the same extent. For example, in an earlier study we have demonstrated that diabetes physicians and nurse educators are prone to misinterpret the effects of diabetes prevention studies depending on the format of the presentation of the results [32,33]. Overall, science literacy is low among physicians [34].…”
Section: Patient Centredness and Shared Decision Makingmentioning
confidence: 99%